2004
DOI: 10.1159/000078388
|View full text |Cite
|
Sign up to set email alerts
|

Candidacy for the Bone-Anchored Hearing Aid

Abstract: The BAHA (bone-anchored hearing aid) is a bone conduction hearing aid with percutaneous transmission of sound vibrations to the skull. The device has been thoroughly evaluated by various implant groups. These studies showed that, in audiological terms, the BAHA is superior to conventional bone conduction devices. In comparison with air conduction devices, the results are ambiguous. However, a positive effect is found with respect to aural discharge. The most powerful BAHA can be applied to patients with a sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 15 publications
(27 reference statements)
2
41
1
2
Order By: Relevance
“…Numerous studies performed on a large number of patients have demonstrated that the Baha system oVers far better results than conventional bone-conduction hearing aids in both adults and children, with substantial improvement in both tonal and speech audiometry [3,[23][24][25]. This is easy enough to explain if we consider that direct (percutaneous) conduction is more eVective than transcutaneous conduction, which, as we know, attenuates the signal by 10-15 dB [26].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Numerous studies performed on a large number of patients have demonstrated that the Baha system oVers far better results than conventional bone-conduction hearing aids in both adults and children, with substantial improvement in both tonal and speech audiometry [3,[23][24][25]. This is easy enough to explain if we consider that direct (percutaneous) conduction is more eVective than transcutaneous conduction, which, as we know, attenuates the signal by 10-15 dB [26].…”
Section: Discussionmentioning
confidence: 93%
“…This makes it possible to use the Baha ampliWer at lower levels, with a lower rate of distortion compared to traditional bone-conduction transducers [27]. Furthermore, compared to them the Baha system yields better results in language comprehension tests, which can be attributed to the better performance achieved in the highfrequency range, which is widely known to be fundamental for good speech discrimination [25]. It is also important to consider that the application of a conventional bone-conduction hearing aid often leads to local problems such as irritated skin and itching in the retromastoid area, due to the pressure of the transducer on the skin [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be used effectively by pediatric and adult patients who are not suitable surgical candidates for canalplasty. Baha implant has to be surgically implanted to obtain skin penetrating coupling [2,3]. The indications for Baha implant are classified as otological or audiological.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the role of TA in the selection of transcutaneous devices is warranted. Transcutaneous implants are subject to attenuation of sound due to less effective transmission of the signal compared to direct bone conduction [Hakansson et al, 1984;Snik et al, 2004]. Attenuation for transcutaneous stimulation varies considerably, and threshold shift for transcutaneous versus percutaneous stimulation can vary by almost 20 dB [Mylanus, 1994].…”
Section: Discussionmentioning
confidence: 99%